Role of endobronchial and endoscopic ultrasound in pulmonary medicine - Gompelmann, Daniela; Herth, Felix (Respiration, 2014)
In the last decade, endobronchial ultrasound (EBUS) has evolved into an important tool for diagnostic bronchoscopy in daily practice. EBUS has established as a standard for the diagnosis of hilar or mediastinal lymphadenopathy, as a guidance technique for peripheral pulmonary lesions and for the evaluation of tumor involvement of the tracheobronchial wall or mediastinum. In the meantime, EBUS has also taken a significant role in mediastinal staging in lung cancer patients. However, EBUS plays not only a role in the diagnosis of malignancies, it is also important for the diagnosis of benign disorders.